Engineering of maltose-binding protein to employ a poly-arginine tag and improve protein purification - Wochinski, Abby (My University, 2007)
Maltose binding protein (MBP), a solubility-enhancing fusion protein, has demonstrated great success in the application of protein purification when fused to a protein of interest. It has already been engineered to include a poly-histidine tag to allow for purification via Immobilized Metal Affinity Chromatography (IMAC). I have engineered this protein to include a poly-arginine tag, which would promote a cation-exchange purification step while maintaining the solubility-enhancing property of the original MBP. However, the inclusion of the poly-arginine tag did not significantly impact the elution profile of MBP during cation-exchange chromatography. This lack of purification suggests that the interactions between the positively charged arginine residues and .the negatively charged compounds on the resin were insufficient to affect the salt dependent binding of MBP.
17 p.
Keywords: Biochemistry